Mencari Relevansi Teori dalam Menganalisis Sikap MPR 1998-2000 terhadap Gagasan Negara Hukum yang Demokratis - Margarito Kamis (Jurnal Hukum IUS QUIA IUSTUM, 2000)
A sociological approach is the relevant and appropriate one to clarify the current phenomena in line with administrative law. Its significance can betraced from three views; firstly, interactionand interrelationship among the phenomena: law, economy, politic and culture have been considered more important toward aspects of the current state affairs issue. Secondly,  hope, perception, and value are continuously developed and rapidly changeable. Theoretically and practically, the change has an influence to the state affairs system. Thirdly, historically the state affairs form of a country provides as well as constitutes a reflection of dynamic and interaction among politic, economy, law, and cultural dimensionsat that time. Ethical quality and state affair philosophy of a country should be investigated and put into their context.